KEANEKARAGAMAN JENIS TUMBUHAN PAKAN ORANGUTAN (Pongo pygmaeus wurmbii) DI KAWASAN HUTAN KONSERVASI PT. KAYUNG AGRO LESTARI (KAL) KABUPATEN KETAPANG - Alzaqi, Muhammad; Prayogo, Harri (Universitas Tanjungpura, 2018)
Orangutans (Pongo pygmaeus) are endemic to the island of Borneo whose existence is threatened with extinction. As a result of its population which has continued to decline over the past few decades, the International Union for Conservation Nature (IUCN) raised the status of Bornean orangutans from endangered to critical (Critically endangered). The study was conducted in the conservation forest area of PT. Kayung Agro Lestari (KAL) District Ketapang. This study aims to determine the diversity of species of feed for orangutans (Pongo pygmaeus Wurmbii) and to determine the availability of feed for orangutans in their original habitat. The method used is purposive sampling by making a double plot that is placed randomly at the location found in the type of orangutan feed. The results of this study found as many as 38 types of plants, 30 species are food sources and 8 species are not sources of feed. Analysis of the Important Value Index (INP) data of the largest value at all growth rates for tree level and seedlings was dominated by jungkang type (Palaquium leiocarpum) with a value of 33.83% and 54.01%. The level of the pole is dominated by the type of guava change (Syzygium sp1) with a value of 26.69%, while for the stake level is dominated by the type of pandanus (Pandanus sp) with a value of 47.67%.Keywords: Feed, Orangutan, Species diversity